PEMANFAATAN FITUR TEMPLATE PADA CANVA UNTUK MENINGKATKAN EFISIENSI DAN KREATIVITAS SISWA DI SMP 3 IBRAHIMY - Zaehol Fatah; Ummariyatul Fitriyah (Jurnal Padamu Negeri, 2026)
This study aims to examine the impact of using Canva templates on students' work efficiency and creativity. Canva is a web-based platform that provides a wide range of ready-to-use design templates to support teaching and learningactivities. Previous studies have shown that Canva is an effective learning medium that enhances students' engagement, creativity, and productivity. Thisstudy employed a literature review method to analyze findings from relevant scientific publications. The results indicate that Canva's template features helpstudents complete their tasks more efficiently, foster creativity, and create a more engaging and interactive learning environment. Therefore, the use of Canva templates can serve as an effective alternative learning medium to improve the quality of teaching and learning at SMP 3 Ibrahimy.